2020
DOI: 10.22270/jddt.v10i3-s.4182
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Contents and Antioxidant Properties of Algerian Arbutus unedo L. Extracts

Abstract: Arbutus unedo L. is a plant widely distributed in the Mediterranean basin and North Africa, frequently used in traditional folk medicine to treat diabetes and arterial hypertension. This study aims to evaluate the phenolic composition and antioxidant activity of ethyl acetate (EA.E) and n-butanolic (But.E) extracts prepared from leaves of Arbutus unedo. Total phenolic and flavonoids contents were determined spectrophotometrically. The antioxidant activity was evaluated using DPPH•, OH•, H2O2, O•-2, ß-carotene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Several studies have confirmed the importance of these compounds in this plant (Hmaidosh et al, 2020;Jurič et al, 2020;Erkekoglou et al, 2017;Bertsouklis et al, 2021). Therefore, the TPC was about 192 (mg GAE /g DW) and 836.51 (μg GAE/mg extract) in Algeria (Bakchiche et al, 2013;Laouicha et al, 2020), 32 (mg GAE/g DW) in Tunisia (Habachi et al, 2022) and 37.3 (g GAE/g of DW) in Morocco (Mrabti et al, 2017). A study conducted in Croatia revealed a composition ranging between 553 and 850 (mg GAE/100g DW).…”
Section: Polyphenols Total Content (Mg Gae/ 100 G Extract)mentioning
confidence: 86%
“…Several studies have confirmed the importance of these compounds in this plant (Hmaidosh et al, 2020;Jurič et al, 2020;Erkekoglou et al, 2017;Bertsouklis et al, 2021). Therefore, the TPC was about 192 (mg GAE /g DW) and 836.51 (μg GAE/mg extract) in Algeria (Bakchiche et al, 2013;Laouicha et al, 2020), 32 (mg GAE/g DW) in Tunisia (Habachi et al, 2022) and 37.3 (g GAE/g of DW) in Morocco (Mrabti et al, 2017). A study conducted in Croatia revealed a composition ranging between 553 and 850 (mg GAE/100g DW).…”
Section: Polyphenols Total Content (Mg Gae/ 100 G Extract)mentioning
confidence: 86%
“…Like reductones, polyphenols may interact with free radicals to convert them into more stable compounds and inhibit free radical chain reactions. 34 According to Zhang et al 2 E. dulcis plants contain Gallocatechin gallate, epicatechin gallate, and catechin gallate compounds from ethanol extract were reported to have potent antioxidant effects. In addition, other flavonoid compounds contained in this plant, namely fisetin, diosmetin, luteolin, and tectorigenin from methanol/ethyl acetate extract, were also reported to have antioxidant activity.…”
Section: Minimum Inhibitory Concentration (Mic) Test and Minimum Bact...mentioning
confidence: 99%
“…Many researchers reported various pharmacological applications of C. dichotoma such as Anti-ulcer 1 , Contraceptives 2 , anti-inflammatory 3,4,5,6 anthelmintic, analgesic, anticancer 4,7,8 , Antioxdant 8,9 , antimicrobial 10 , antifungal 10 , hepatoprotective 11 and diuretic purposes and for treating digestive system, respiratory, urogenital, cardiac, vascular and blood disorders. C. dichotoma is a promising source of natural antioxidants which possess remarkable therapeutic action as inflammatory activity and may serve as food ingredients 12,13,14,15 . Thus objectives of the present review are to provide an overview of the uses of C. dichotoma as herbal antioxidant.…”
Section: Introductionmentioning
confidence: 99%